Marriage Is Scary Dalam Perspektif Hukum Keluarga Dan Hukum Positif - Melinda Sari (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to: (1) analyze the perspectives of Islamic family law and Indonesian positive law regarding the “marriage is scary” phenomenon, which refers to fear or hesitation toward marriage due to economic, social, social media influences, and personal or environmental experiences; and (2) examine normative solutions to address this phenomenon in the future. This research employs a normative legal method with statutory, historical, conceptual, and case approaches. The data were analyzed qualitatively through normative analysis based on library research, including the examination of legislation, Islamic family law literature, legal doctrines, and relevant legal theories. From the perspective of Islamic family law, marriage is viewed as a means to achieve tranquility (sakinah), love (mawaddah), and compassion (rahmah), grounded in faith, responsibility, and noble character. Islam encourages—and in certain circumstances obliges—marriage for individuals who are physically and mentally prepared and fear falling into sinful conduct. Meanwhile, Indonesian positive law is considered not yet fully responsive to the “marriage is scary” phenomenon, as there remain gender role imbalances and multiple interpretations within Law Number 1 of 1974 on Marriage. Normative solutions include: (1) at the dharuriyyah (primary necessity) level strengthening premarital education, economic readiness, communication skills, and information literacy; (2) at the hajiyyah (secondary necessity) level enhancing social support and scholarly engagement; and (3) at the tahsiniyyah (tertiary necessity) level cultivating gratitude, forgiveness, and personal self-improvement.